Feeding microalgae meal (All-G Rich (TM); Schizochytrium limacinum CCAP 4067/2) to beef heifers. II: Effects on ground beef color and palatability - Phelps, Kelsey J.; Drouillard, James S.; O'Quinn, Travis; Burnett, D. D.; Blackmon, Terri L.; Axman, J. E.; Van Bibber-Krueger, Cadra L.; Gonzalez, John M. (My University, 2017)
The objective of this study was to examine the effects of feeding microalgae meal (All-G Rich, Schizochytrium limacinum CCAP 4087/2; Alltech Inc., Nicholasville, KY) to finishing heifers on 85% lean and 15% fat (85/15) ground beef PUFA content, palatability, and color stability. Crossbred heifers (n = 288; 452 +/- 23 kg initial BW) were allocated to pens (36 pens and 8 heifers/pen), stratified by initial pen BW (3,612 +/- 177 kg), and randomly assigned within strata to 1 of 4 treatments: 0, 50, 100, and 150 g center dot heifer(-1) center dot d(-1) of microalgae meal. After 89 d of feeding, a subset of heifers (3/pen) was harvested and the rectus femoris, vastus lateralis, vastus medialis, and vastus intermedius were collected for processing into ground beef. At 42 d postmortem, 85/15 ground beef was formulated and formed into 112-g patties and fatty acid composition, subjective palatability, and 96-h retail color stability analyses were conducted. Increasing dietary microalgae meal concentration increased ground beef 20: 5n-3 and 22: 6n-3 fatty acids (quadratic, P < 0.01). There was a treatment x hour interaction for all color attributes (P < 0.01). On d0, microalgae tended (P = 0.08) to decrease L*, but patties had similar L* values the remainder of display (P > 0.12). Feeding microalgae meal affected (P = 0.02) b* at 24 h and decreased (linear, P = 0.08) b* at 48 h. From h 0 to 36 of display, microalgae affected redness of patties (P < 0.02), and from 48 to 72 h, microalgae meal decreased a* value (linear, P < 0.04). Microalgae meal did not impact sensory panel firmness, overall tenderness, or juiciness scores (P > 0.20) but tended to affect (P = 0.10) cohesiveness scores. As the amount of microalgae meal fed to heifers increased, beef flavor intensity decreased (linear, P < 0.01) and off-flavor intensity increased (quadratic, P < 0.05). Surface oxymyoglobin and metmyoglobin were impacted by microalgae meal from 12 to 36 h of display (P < 0.01). From 48 to 84 h of display, feeding microalgae meal to heifers decreased (linear, P < 0.09) surface oxymyoglobin and increased (linear, P < 0.02) surface metmyoglobin of patties. Although feeding microalgae meal to heifers increases the PUFA content of 85/15 ground beef, there are undesirable effects on flavor and color stability.
Citation: Phelps, K. J., Drouillard, J. S., O'Quinn, T. G., Burnett, D. D., Blackmon, T. L., Axman, J. E., . . . Gonzalez, J. M. (2016). Feeding microalgae meal (All-G Rich (TM); Schizochytrium limacinum CCAP 4067/2) to beef heifers. II: Effects on ground beef color and palatability. Journal of Animal Science, 94(9), 4030-4039. doi:10.2527/jas2016-0488
Keywords: Color; Fatty Acid; Ground Beef; Microalgae; Palatability; Fatty-Acid-Composition